Representation of Ideology in K.H Said Aqil Shiradj’s Speech: Critical Discourse Analysis - Moh Kavin Lidinillah (JELP Journal of English Language and Pedagogy, 2022)
The purpose of this study is to reveal the ideology contained in the text of KH Said Aqil Shiradj's speech on the commemoration of the 73rd NU Muslim celebrations. The data obtained in video form was then transcribed in text form. In analyzing the data, the researcher uses Van Dijk's critical discourse analysis approach which consists of text analysis in the form of macro, super, and micro structures, analysis of social cognition, and social analysis. Text analysis seeks to analyze the themes, structure, and linguistic features of speech. The analysis of social cognition seeks to analyze the production of speech texts and social analysis to analyze the discourse that develops in society. From the two speeches analyzed there are ideologies, namely religious national ideologies. This ideology is in line with the ideology adopted by NU which is based on thereligious scriptures of Muslims. With this ideology, KH Said Aqil Shiradj uses the basis of the Islamic religion that comes from the hol book of Muslims which is used as a basis in creating a national spirit to play a role in maintaining the unity and integrity of the Indonesian state